Genotype by Environment Interaction on Grain Yield Stability and Iron and Zinc Content in OPV of Pearl Millet in Ghana Using the AMMI Method - Peter Anabire Asungre; Richard Akromah; Alexander Wireko Kena; Prakash Gangashetty (International Journal of Agronomy)
Twenty-two open-pollinated varieties (OPVs) of pearl millet (Pennisetum glaucum) genotypes were tested in two locations for three seasons in Ghana to estimate the magnitude of genetic variability, heritability, and stability for grain yield and related traits and grain micronutrients among the varieties. General analysis of variance within and across locations and years revealed very highly significant variability (p<0.01) among the genotypes. The additive main effects and multiplicative interaction (AMMI) analyses revealed significant genotype × environment interaction (GEI) that influenced the relative ranking of genotypes across the environments. Genotypic variance (σ2g) contributed a greater proportion of the phenotypic variance (σ2p) for plant height (530.31) and grain Fe content (34.72). Broad-sense heritability (hbs2) varied widely from 24.82% for grain yield to 77.53% in days to flower. Phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) for all traits, indicating strong play of environment on trait expressions. 11 out of the 22 OPVs were stable for grain yield and micronutrients across environments for the three-year period and included GB 8735 and ICMV 221 Wbr and SOSAT-C88.